Upshot of Exchange Rate on Export and Import of Agricultural Production in Bangladesh - Tahrim, Farian; Urbee, Afrida Jinnurain; Hasan, Md. Atik; Akther, Tanjina (Economics, Business, Accounting & Society Review, 2023)
An important factor in trade is the currency's exchange rate and fluctuation of exchange rate is very concerning issue in current period over the world. Bangladesh, a developing economy, depends mostly on agriculture sector, recent period’s fluctuation of exchange rates of the country influences its export and import of the agricultural production.  This research examines how the real exchange rate affects agricultural production's import and export between 1977 and 2015 in Bangladesh. Variables like Total Agricultural Production, Real Gross Domestic Product, Exchange rates, and Exports and Imports of Agricultural Product have been taken for this study. Ordinary Least Square Method (OLS) and other related econometrical techniques are applied to find the association among indicators. The research indicates that the exchange rate shows no discernible effect on the import and export of agricultural production in Bangladesh. However, Real Gross Domestic Product (GDP) of the country portraits no significant influence on agricultural exports while portraits positive significant influence on agricultural imports. This research contributes to appropriate policies and actions that must be implemented at an equitable level.